Energy and Exergy Analysis of Kalina Cycle for the Utilization of Waste Heat in Brine Water for Indonesian Geothermal Field - Nasruddin, Nasruddin; Sidiq, Agus Noor; Mohamad, Abdulmajeed; Usvika, Rama (Makara Journal of Technology, 2015)
The utilization of waste heat in a power plant system—which would otherwise be released back to the environment—in order to produce additional power increases the efficiency of the system itself. The purpose of this study is to present an energy and exergy analysis of Kalina Cycle System (KCS) 11, which is proposed to be utilized to generate additional electric power from the waste heat contained in geothermal brine water available in the Lahendong Geothermal power plant site in North Sulawesi, Indonesia. A modeling application on energy and exergy system is used to study the design of thermal system which uses KCS 11. To obtain the maximum power output and maximum efficiency, the system is optimized based on the mass fraction of working fluid (ammonia-water), as well as based on the turbine exhaust pressure. The result of the simulation is the optimum theoretical performance of KCS 11, which has the highest possible power output and efficiency. The energy flow diagram and exergy diagram (Grassman diagram) was also presented for KCS 11 optimum system to give quantitative information regarding energy flow from the heat source to system components and the proportion of the exergy input dissipated in the various system components.